Effects of NDVI/Meteorological Elements on Actual Evapotranspiration in Loess Plateau over Last 20 Years - HAN Yuping; XU Dan; HUANG Huiping; JIA Dongdong; PEI Duo; ZHANG Junfeng (Renmin Zhujiang)
Given that the Grain for Green Program significantly enhances the vegetation coverage in the Loess Plateau and that global warming keeps worsening,studying the spatio-temporal distribution law of the evapotranspiration (ET) in the Loess Plateau and the combined influences of the normalized difference vegetation index (NDVI) and meteorological elements on the ET can guide the comprehensive management of the water resources in the plateau.Spatial regression analysis,Morlet wavelet analysis,and principal component analysis are performed to examine the spatio-temporal evolution characteristics of the ET in the Loess Plateau during the three periods of the whole year,the growing season,and the non-growing season over 2001—2020 and the combined influences of NDVI and meteorological elements with MOD16A2 ET,MOD13Q1 NDVI,and meteorological data.The results support the following conclusions:① ET increases significantly in all the three periods,with the growth rate for the whole year higher than that for the growing season and much higher than that for the non-growing season.The three periods all have a first main cycle of 14 a.ET decreases from southeast to northwest both in the whole year and the growing season,and the ET in the non-growing season is lower than that in the whole year and that in the growing season.The higher value is in the west and the south,and the spatial distribution of the interannual variation of ET is consistent with that of ET.② NDVI also increases significantly in all the three periods,and the spatial distribution of its value is consistent with that of ET.Precipitation increases remarkably in the whole year and in the growing season,with no marked growth in the non-growing season.No obvious increase trends in temperature and wind speed are observed in the three statistics periods.The spatial distribution laws of precipitation and temperature are largely consistent with that of ET.③ The contribution of each influencing factor to the change in ET varies with the period.Specifically,the first principal factors in the growing season,the non-growing season,and the whole year are respectively wind speed,temperature,and NDVI,NDVI,precipitation,and temperature,and NDVI and precipitation.